Universal Marker and Detection Tool for Human Sarcoma Circulating Tumor Cells - Satelli, Arun; Mitra, Abhisek; Cutrera, Jeffry J.; Devarie, Marcos; Xia, Xueqing; Ingram, Davis R.; Dibra, Denada; Somaiah, Neeta; Torres, Keila E.; Ravi, Vinod; Ludwig, Joseph A.; Kleinerman, Eugenie S.; et al. (Cancer research (Chicago, Ill.), 2014)
To date, no specific marker exists for the detection of circulating tumor cells (CTC) from different types of sarcomas, though tools are available for detection of CTCs in peripheral blood of patients with cancer for epithelial cancers. Here, we report cell-surface vimentin (CSV) as an exclusive marker on sarcoma CTC regardless of the tissue origin of the sarcoma as detected by a novel monoclonal antibody. Utilizing CSV as a probe, we isolated and enumerated sarcoma CTCs with high sensitivity and specificity from the blood of patients bearing different types of sarcoma, validating their phenotype by single cell genomic amplification, mutation detection, and FISH. Our results establish the first universal and specific CTC marker described for enumerating CTCs from different types of sarcoma, thereby providing a key prognosis tool to monitor cancer metastasis and relapse. Cancer Res; 74(6); 1645–50. ©2014 AACR.